Revolución ciudadana: Tanto para tan poco - Paredes, Pablo Lucio (2013)
This book reflects the traditional way of seeing the economy, since the author insists that the Government Sector should not become the central axis of the economy, since he suggests that the greatest source of employment generation should be private enterprise.